Practical and efficient synthesis of aryl trifluoromethyl sulfones from arylsulfonyl chlorides with Umemoto's reagent II. Issue 5 (30th January 2020) - Zhou, Xiaocong; Hu, Dufen; He, Xinyi; Li, Yuanqiang; Chu, Youqun; She, Yuanbin
Graphical abstract: Highlights: A new practical and effective method for ArSO2 CF3 from ArSO2 Cl. The trifluoromethyl source is safe Umemoto's reagent II. Broad substrate scope containing heteroaryl- and alkyl-sulfonyl chlorides. Transition-metal-free and mild conditions. Abstract: A practical and efficient method for the synthesis of aryl trifluoromethyl sulfones has been developed by a tandem reaction of arylsulfonyl chlorides with Umemoto's reagent II. The advantageous features of this method are simple operation, mild reaction conditions, wide scope of substrates, high yield of products, and easy scalability.